Product Marketing by Frontliners - Rosianti, Dewi Azizah; Dyah Widowati (IJESS International Journal of Education and Social Science, 2025)
This research aims to analyze the role of frontliners in improving marketing effectiveness at PT Pegadaian, especially at Mulyosari Branch Surabaya. This research uses a descriptive qualitative approach with a field research method involving direct observation and interviews. Data were collected through direct observation and discussions with frontliners regarding the marketing of Pegadaian products. The analysis focused on the key factors that influence the success of marketing strategies, including the skills and knowledge required by frontliners. The results showed that frontliners at PT Pegadaian have a crucial role in providing services, providing product information, and engaging in marketing activities. However, frontliners' dual roles as marketing officers, collateral managers, cashiers and estimators limit their time to fully engage in marketing tasks, especially during busy times. To overcome this, PT Pegadaian implements strategies such as involving back-office staff in marketing activities and organizing regular promotional schedules such as canvassing activities in the market. These efforts aim to expand marketing reach and increase customer engagement, ultimately strengthening customer loyalty and trust in PT Pegadaian's services.